Global Research Trends in Knowledge Management in Higher Education: A Bibliometric Analysis - Altawe, Mohamed Aghel; Yakhlf, Mahmoud Abdualaziz Y.; Md Kassim, Aza Azlina (International Review of Management and Marketing, 2026)
This study provides a comprehensive analysis of KM research, highlighting emerging trends and critical gaps. It offers practical insights for researchers and policymakers to guide KM strategy development in HEIs. This study conducts a comprehensive bibliometric analysis of knowledge management (KM) research in Scopus-indexed publications from 1998 to 2024, with a particular focus on developments within higher education institutions (HEIs). The research aims to trace the evolution of KM scholarship, identify influential contributors, and uncover emerging thematic trends. A total of 696 articles were analyzed using both quantitative and qualitative bibliometric techniques, including publication and citation analysis, co-authorship networks, and keyword co-occurrence. Performance analysis assessed scholarly output and impact, while science mapping facilitated by VOS-viewer visualized intellectual structures and research clusters. The findings reveal a significant growth in KM research, peaking in 2023 with 72 publications. Northwestern Polytechnical University stood out in citation impact, and the United Kingdom was identified as the most prolific contributor. The journal Computers and Education led in output, and the most cited article addressed KM readiness in HEIs. Notably, artificial intelligence (AI) and digital transformation emerged as promising directions for future research. This study provides valuable insights into the development of KM in the higher education sector and offers strategic implications for researchers, academics, and policymakers aiming to enhance institutional innovation and competitiveness.